DINAMIKA HUBUNGAN ETIOPIA DAN MESIR DALAM MASA PEMBANGUNAN GRAND ETHIOPIAN RENAISSANCE DAM (GERD) DI SUNGAI NIL BIRU TAHUN 2015-2020 - Indah Sakinah; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Ethiopia has not benefited from the water from the Nile for a long time, even though geographically the Blue Nile is located in the upper reaches of the river, most of which are in the territory of Ethiopia. However, due to the historical treaties of 1929 and 1959 between Egypt, Sudan, and the United Kingdom, it strengthened the Egyptian dominance to manage and regulate water rights in the Nile. But in 2011 Ethiopia announced it would build a giant water dam called the Grand Ethiopian Renaissance Dam (GERD) to boost economic growth.  This study uses a Mercantilism perspective with country-level analysis. The theory used in this research is the International Cooperation Theory from K.J Holsti. The qualitative method in this study uses secondary data with literature studies, using supporting data collected and references from several books, journals, articles, and various media related to this research. This study shows that Ethiopia asks for assistance from upstream and downstream to jointly agree to this development by agreeing called the Nile Basin Initiative Basin (NBI) and the Cooperative Framework Agreement (CFA) to further facilitate Ethiopia in building this dam. However, the Ethiopian effort was criticized and rejected by Egypt. From 2015 to 2020 there is an ever-changing dynamic in relations between Ethiopia and Egypt. This is because these two countries have the same national interest in maintaining the right to water in the Nile for the welfare of the people of each country. Keywords : GERD, NBI, CFA, and Ethiopiam dam.